1997
DOI: 10.1007/s001250050667
|View full text |Cite
|
Sign up to set email alerts
|

Islet transplantation in IDDM patients

Abstract: Several reports have already shown that intrahepatic transplantation of purified islets can replace the pancreatic endocrine function in diabetic patients without major side effects for either the patients or their liver function [1][2][3][4][5]. Despite these encouraging results, the data of the International Islet Transplant Registry [6] are not as encouraging: in the 1989-1994 period only 28 out of 180 patients (16 %) maintained insulin independence for more than one week.This paper reports the experience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 15 publications
3
38
0
1
Order By: Relevance
“…Pancreata were obtained from heart-beating cadaveric multiorgan donors through the North Italian Transplant Organization. Islets were isolated according to a modification of the automated method (43,44). Samples of the pancreas and samples of isolated islets were taken for histological examination and for in vitro study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreata were obtained from heart-beating cadaveric multiorgan donors through the North Italian Transplant Organization. Islets were isolated according to a modification of the automated method (43,44). Samples of the pancreas and samples of isolated islets were taken for histological examination and for in vitro study.…”
Section: Methodsmentioning
confidence: 99%
“…Percutaneous trans-hepatic injection (under local anesthesia) was performed according to the protocol approved by the local ethics committee. All patients were already under immunosuppression therapy with steroids and cyclosporine for a previous kidney transplant (44). After islet transplantation, the therapy was changed as follows: antilymphocyte globulin (125 mg/day for 10 days; IMTIX, Marseille, France), cyclosporine (7.5 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 ), mycophenolate mofetil (2 g/day), and methylprednisone (500 mg immediately before surgery, 0.25 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 for 2 months after surgery, then lowered to 5 mg/day).…”
Section: Methodsmentioning
confidence: 99%
“…Islets were cultured in M199 medium supplemented with 10% FCS, 1% L-glutamine, 100 units/ml penicillin, and 100 g/ml streptomycin and incubated at 30°C in 5% CO 2 and 95% humidified air for 2-48 h. Islets were tested for sterility, endotoxin (Chromogenic LAL test; BioWhittaker, Walkersville, MD), and Mycoplasma (Mycoplasma detection kit; Boehringer Mannheim, Indianapolis, IN). Islets were infused in the liver according to the protocol approved by our institutional review board, as reported previously (18,19). In brief, an ultrasound imager was used for guidance during portal vein puncture with a 22-gauge needle under local anesthesia.…”
Section: Islet Transplantationmentioning
confidence: 99%
“…Diabetes 50:277-282, 2001 W e have recently shown that successful intraportal islet transplantation can normalize hepatic glucose production and insulin action in type 1 diabetic patients with a kidney transplant (1). This procedure, now performed in several centers worldwide (2)(3)(4)(5)(6), is relatively safe, noninvasive (percutaneous puncture of the liver), and repeatable. The major factors limiting the large-scale application of islet graft in diabetic patients receiving chronic immunosuppression for a kidney graft are 1) the low percentage of patients reaching insulin independence and a complete normalization of glucose homeostasis (1) and 2) the limited survival of fully successful grafts.…”
mentioning
confidence: 99%
“…The major factors limiting the large-scale application of islet graft in diabetic patients receiving chronic immunosuppression for a kidney graft are 1) the low percentage of patients reaching insulin independence and a complete normalization of glucose homeostasis (1) and 2) the limited survival of fully successful grafts. Most diabetic patients receiving an islet graft achieve only partial function and a reduction of the pretransplant insulin requirement (2-6); they are characterized by fasting C-peptide concentrations in the near-normal range, but frankly abnormal fasting glucose and GHb values (1)(2)(3)(4)(5)(6). In the last decade, we (7-10) and others (11,12) found that protein and lipid metabolism had greater sensitivity to acutely infused insulin than did glucose metabolism, both in diabetes and uremia.…”
mentioning
confidence: 99%